Memristor based circuit design using charge and attached capacitor. (September 2016) - Bagheri-Soulla, A.A.; Ghaznavi-Ghoushchi, M.B.
Abstract: Memristor is a non-linear circuit element with unique behavior. Specifications of this device complicate memristor based circuit design. Ideal memristor is the function of total applied charge so it can be expressed and controlled in terms of charge only. On the other hand, generic and extended memristors could not be modeled using charge only equations, therefor an extension is required. The aim of this paper is to introduce a new memristive circuit design approach based on charge and attached capacitor. The main benefit of this approach is to change the rule of time from a design parameter into a design condition. Our approach is based on instantaneous charging and branching of an attached capacitor with target memristor. Among known memristors, RRAM is used in this work thanks to its emergent properties and well investigated theory and models. Two RRAM models are used in this paper, which can be grouped into two classes of ideal generic and extended memristors. The ideal generic based model is not realistic but is used to explain the design concept. The proposed methodology is applied to design new memristor based digital to analog converters. During our work, we developed some additional blocks, which can be used in other analog applications. The circuit level simulations are performed using SPICE to evaluate design approaches.